3-Nitro-3, 4-dihydrocoumarins: valuable precursors for the synthesis of enantiomerically enriched masked quaternary α-amino acid derivatives with a 3, 4-dihydrocoumarin scaffold. Issue 44 (31st October 2019) - Lv, Dan; Zhao, Min; Wang, Youming; Zhou, Zhenghong
Abstract : A bifunctional squaramide catalysed asymmetric [4 + 2] cyclization has been developed, which provides an efficient approach for the synthesis of novel chiral masked quaternary α-amino acid derivatives with a 3, 4-dihydrocoumarin scaffold. Abstract : A bifunctional squaramide catalyzed enantioselective formal [2 + 4] annulation reaction with 3-nitro-3, 4-dihydrocoumarins and ortho -quinone methide has been developed. Novel chiral masked quaternary α-amino acid derivatives with a 3, 4-dihydrocoumarin scaffold are obtained in a highly stereocontrolled manner. Representative transformation of the annulation product to a biologically important quaternary α-amino acid derivative is achieved without any appreciable loss in the diastereo- and enantioselectivity.